PENERAPAN PENDEKATAN MODEL-ELICITING ACTIVITIES UNTUK MENINGKATKAN KEMAMPUAN BERPIKIR KRITIS DAN KREATIF SISWA - Ibnu Imam Al Ayyubi; Murharyana; Rifqi Rohmatulloh (Jurnal El-Audi, 2023)
Students' creative and critical thinking skills are still low, so alternative learning is needed that can develop students' creative and critical thinking abilities. This study aims to improve students' creative and critical thinking abilities and mathematical dispositions based on their cognitive stage using the Model-Eliciting Activities approach. The results showed that: (1) knowing the increase in creative and critical thinking abilities and mathematical dispositions of students based on their cognitive stage whose learning used the Model-Eliciting Activities approach with students whose learning used the Problem Based Learning approach; (2) finding out whether there is an association of increasing creative and critical thinking abilities and students' mathematical disposition based on their cognitive stage between the high, medium and low groups after students receive learning using the Model-Eliciting Activities approach. Based on the results of statistical and descriptive data processing, information is obtained that: (1) the increase in creative and critical thinking abilities and mathematical dispositions based on their cognitive stage in students who get learning through the Model-Eliciting Activities approach is better than students who get learning with the Problem Based Approach Learning, (2) there are an association of creative and critical thinking skills between high, medium, and low group students, while creative thinking abilities and mathematical dispositions, as well as critical thinking skills and mathematical dispositions, do not have associations between high, medium, and low group students.